2000
DOI: 10.1161/01.cir.101.20.2382
|View full text |Cite
|
Sign up to set email alerts
|

AT 1 Receptor Agonistic Antibodies From Preeclamptic Patients Cause Vascular Cells to Express Tissue Factor

Abstract: Background-We recently described autoantibodies (angiotensin-1 receptor autoantibodies, AT 1 -AA) directed at the AT 1 receptor in the serum of preeclamptic patients, whose placentas are commonly infarcted and express tissue factor (TF). Mechanisms of how AT 1 -AA might contribute to preeclampsia are unknown. We tested the hypothesis that AT 1 -AA cause vascular smooth muscle cells (VSMC) to express TF. Methods and Results-IgG from preeclamptic patients containing AT 1 -AA was purified with anti-human IgG colu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
140
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(149 citation statements)
references
References 42 publications
7
140
0
Order By: Relevance
“…According to present data, AT 1 -AAs were suggested to have similar effects. Dechend et al reported that AT 1 -AAs induced signaling in vascular cells including AP-1 and NF-κB activation (10,11). Both of these nuclear factors participate in inflammation (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to present data, AT 1 -AAs were suggested to have similar effects. Dechend et al reported that AT 1 -AAs induced signaling in vascular cells including AP-1 and NF-κB activation (10,11). Both of these nuclear factors participate in inflammation (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…AT 1 -AAs induced signaling in vascular cells and trophoblasts including activator protein-1 (AP-1) and nuclear factorkappa B (NF-κB) (10,11), and activated calcineurin-NFAT (nuclear factor of activated T cells) through increased intracellular Ca 2+ mobilization in Chinese hamster ovary cells transferred with the rat AT 1A receptor (12). However, there were limited data related to the role of AT 1 -AAs in pathogenesis of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…The placenta is a key component in the pathophysiology of PE particularly those with reduced placental perfusion. Many investigators believe that preeclampsia is the result of vasoactive and inflammatory mediators secreted by the placenta acting on the vascular endothelium leading to vasoconstriction of the smooth muscle [1,2]. These mediators are likely secreted from trophoblast cells (TCs) in response to placental hypoxia/ischemia and shallow cytotrophoblast invasion acting on vascular endothelium [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that multiple mechanisms contribute to the increased vascular resistance during PE, including increased vascular sensitivity to angiotensin II (ANG II) [4,5], the presence of angiotensin II receptor-1 (AT 1 ) autoantibody [2,6], an imbalance between the vasoconstrictor thromboxane (TX) and decreased vasodilator prostacyclin (PGI2) [7,8], and altered endothelin (ET) [9,10] and nitric oxide (NO) [11] levels in both the maternal circulation and in the placenta in women with PE. These alterations may result in a detrimental positive feedback system that promotes inflammation and further vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation